A review of Technology Education in Ireland; a changing technological environment promoting design activity - Leahy, Keelin; Phelan, Pat (International journal of technology and design education, 2014)
In Ireland, Technology Education’s structure and organisation across the levels of education is not delivered or governed in a coherent manner. Technology Education in primary level education, for students between 5 and 12 years of age, does not explicitly exist as a separate subject. In primary level education, Social, Environmental and Scientific Education (Science), encourages a child to examine and appreciate how technology and science impacts on their lives and the environment. It supports children developing design and make skills, and to apply scientific ideas to everyday situations and practical problems (DES in Primary school curriculum, science. Social, environmental and scientific education curriculum, 1999 ). In addition, various initiatives such as the Junior Lego League, supported by the Galway Education Centre, facilitate various perspectives of Technology Education. In second level education, which this paper primarily focuses on, Technology Education exists as a suite of eight subjects, for students of 12–18 years of age. In third level education students can choose from a wide range of bachelor degree programmes in science, technology, engineering or maths. The degree programmes available at third level also include programmes in initial teacher education (ITE). These programmes in initial teacher education are offered by two institutions, and graduate second level teachers to service the second level system. Technology Education in second level education was first introduced to Ireland in 1885. Since this introduction, revisions and changes have occurred, in both the Irish economy and syllabi. In 2006, Technology Education syllabi were revised to include more design activity at senior cycle. These changes reflect the forward thinking of policy makers in reflection of the progression from the industrial era to the information era to the conceptual era. The scope of second level Technology Education in an Irish context is still perceived by many as vocational, though progressive reformations are advancing towards a design-driven framework, grounded in a strong craft practice. This changing technological environment has resulted in the promotion of design activity in second level Technology Education in Ireland. This paper reviews the establishment of design education in Technology Education in the Irish second level education context, where an epistemological shift towards design activity has occurred.